Internet use and addiction among medical students of Universiti Sultan Zainal Abidin,Malaysia - Haque, Mainul; A. Rahman, Nor Azlina; Majumder, M Anwarul Azim; Haque, Seraj Zohurul; M Kamal, Zubair; Islam, Zakirul; Haque, ATM Amdadul; A.Rahman, Nor Iza; Alattraqchi, Ahmed Ghazi (Dovepress, 2016)
The use of Internet has now become indispensable, and the technology has revolutionized the medical education and practice worldwide. Currently, medical students and professionals have an enormous opportunity to keep them always updated with the exponential growth of knowledge because of potential progression of Internet throughout the world that enables them to become a lifelong learner. Internet addiction is a widespread phenomenon among students and academicians at universities in Malaysia. Students use the Internet for recreational purpose and personal and professional development. The Internet has become an integral part of day-to-day life of the university students, including medical students. The aim of the present study was to examine the Internet use and addiction among students of Universiti Sultan Zainal Abidin, Malaysia. Methods: This was a cross-sectional study in which a questionnaire, Internet Addiction Diagnostic Questionnaire, developed by the Center for Internet Addiction, USA, was used. One hundred forty-nine medical students of Universiti Sultan Zainal Abidin participated in this study. Data were analyzed using Statistical Package for the Social Sciences software. Results: The mean scores were 44.9±14.05 and 41.4±13.05 for male and female participants, espectively, which indicated that both the genders were suffering from mild Internet addiction. Conclusion: This study shows almost similar level of Internet usage among medical students irrespective of their socioeconomic background, with no statistically significant (p>0.05) differences, except among the years of study (p=0.007). Overall, from the research data and having worked with this cohort very closely, Universiti Sultan Zainal Abidin medical students can be labeled as wonted and recurring users of the Internet. Nevertheless, it is very difficult to define as Internet addicts or pathological users of the Internet because of small sample size and cross-sectional study.